A New Iterative Method for Suzuki Mappings in Banach Spaces - Junaid Ahmad; Kifayat Ullah; Muhammad Arshad; Zhenhua Ma (Journal of Mathematics)
In this paper, an efficient new iterative method for approximating the fixed point of Suzuki mappings is proposed. Some important weak and strong convergence results of the proposed iterative method are established in the setting of Banach space. An example illustrates the theoretical outcome.